Entornos personales de aprendizaje y competencias investigativas digitales en estudiantes de la Universidad Nacional de Piura - Hidalgo Benites, Lilliam Enriqueta (2023)
This study examines the impact of utilizing Personal Learning Environments on enhancing Digital Investigative Competences in undergraduate students at the National University of Piura. Employing a pre-experimental design, the research evaluated students both prior to and subsequent to their participation in a virtual Pedagogical Program titled “Construction of Personal Learning Environments.” A self-assessment sheet gauging digital investigative skills served as the research instrument. The post-test findings indicated that 97% of the students achieved a medium level of competence, while 2.99% exhibited a high level. None fell within the low proficiency category. Statistical analysis employing the non-parametric Wilcoxon test, with a calculated p-value of Sig (bilateral) = 0.000 < α = 0.05, confirmed the significant influence of Personal Learning Environments on the enhancement of Digital Investigative Competences.